2021
DOI: 10.3390/ijms221910639
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Microglia in Neurodegenerative Diseases: Beneficial Effects of Docosahexahenoic Acid (DHA) Supplied by Food or Combined with Nanoparticles

Abstract: Neurodegenerative diseases represent a major public health issue and require better therapeutic management. The treatments developed mainly target neuronal activity. However, an inflammatory component must be considered, and microglia may constitute an important therapeutic target. Given the difficulty in developing molecules that can cross the blood–brain barrier, the use of food-derived molecules may be an interesting therapeutic avenue. Docosahexaenoic acid (DHA), an omega-3 polyunsaturated fatty acid (22:6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…Of note, in our experimental conditions, metabolic improvement induced by a balanced ω-3:ω-6 PUFAs ratio was not accompanied by weight loss. Thus, in our model, DHA is not likely to influence peripheral lipotoxicity directly but rather to contribute to local protective mechanisms in the brain 70 .…”
Section: Discussionmentioning
confidence: 86%
“…Of note, in our experimental conditions, metabolic improvement induced by a balanced ω-3:ω-6 PUFAs ratio was not accompanied by weight loss. Thus, in our model, DHA is not likely to influence peripheral lipotoxicity directly but rather to contribute to local protective mechanisms in the brain 70 .…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have demonstrated that DHA limits the inflammatory effects likely due to its direct impact on the microglia. 57 The DHA treatment can restore the ramification of Iba1 + cells, influencing a morphological shift away from the amoeboid-like shape and toward the classic ramified morphology with cellular extensions protruding from the cell body with a more permissive, surveillant state. 58 Although robust studies regarding probiotics to mitigate neuroinflammation remain under research, it has been proposed that these microorganisms can be used as immunization agents to promote enhanced immunoregulation via T-reg cells, shifting the immune response toward an anti-inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…DHA + Prob + VD3 exhibited the most significant reduction, suggesting its potential to mitigate microglial activation. Several studies have demonstrated that DHA limits the inflammatory effects likely due to its direct impact on the microglia . The DHA treatment can restore the ramification of Iba1 + cells, influencing a morphological shift away from the amoeboid-like shape and toward the classic ramified morphology with cellular extensions protruding from the cell body with a more permissive, surveillant state .…”
Section: Discussionmentioning
confidence: 99%
“…Three primary types of FA exist and differ based on their saturation levels: saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), and polyunsaturated fatty acids (PUFAs) [18]. SFAs have no double bonds in their carbon atoms, while MUFAs have only one, and PUFAs have two or more [19]. The three types further harbor various physiological effects.…”
Section: Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 99%